C/N Vacancy Co-Enhanced Visible-Light-Driven Hydrogen Evolution of g-C3N4 Nanosheets Through Controlled He+ Ion Irradiation - Wang, Xuening; Wu, Liang; Wang, Zhaowu; Wu, Hengyi; Zhou, Xuemei; Ma, Hongyu; Zhong, Huizhou; Xing, Zhuo; Cai, Guangxu; Jiang, Changzhong; Ren, Feng (Solar RRL, 2019)
Graphitic carbon nitride (g-C3N4) is reported to be a promising metal-free semiconductor for photocatalytic water splitting. However, the performance of g-C3N4 is substantially limited by its insufficient visible-light absorption and low photogenerated charge carrier separation efficiency. In this work, an innovative method (ion irradiation) to efficiently introduce both defined C- and N-vacancies (V-C and V-N) simultaneously into g-C3N4 nanosheets are explored. Unlike traditional chemical methods, by controlling He+ ion fluence, tunable vacancy concentrations are able to be obtained in g-C3N4. Defect-engineered g-C3N4 shows highly improved performance under optimized conditions, the defective g-C3N4 exhibits a significantly higher (2.7-fold) hydrogen evolution rate of 1271 mu molg(-1)h(-1) than that of the g-C3N4 nanosheets under visible light (lambda>420nm) illumination. Meanwhile, the defective g-C3N4 exhibits a significantly enhanced (threefold) photocurrent density as photoanodes for photoelectrochemical (PEC) water splitting. Further characterizations show that the enhanced visible light absorption and an extended charge carrier lifetime, can be ascribed to the presence of C- and N- vacancies. These experimental results are in line with density functional theory (DFT) calculations. Therefore, the present work shows that defect-engineering on g-C3N4 using ion irradiation technique, is an effective, controllable, and defined approach to improve the photocatalytic and PEC water splitting performance of g-C3N4.
CRIS-Team WoS Importer:2019-08-09